Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
CRIS-Team Scopus Importer:2020-10-23
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Electrocatalytic Performance of Titania Nanotube Arrays Coated with MoS2 by ALD toward the Hydrogen Evolution Reaction - Cao, Yuanyuan; Wu, Yanlin; Badie, Clémence; Cadot, Stéphane; Camp, Clément; Quadrelli, Elsje Alessandra; Bachmann, Julien (ACS Omega, 2019)
The electrochemical splitting of water provides an elegant way to store renewable energy, but it is limited by the cost of the noble metals used as catalysts. Among the catalysts used for the reduction of water to hydrogen, MoS2 has been identified as one of the most promising materials as it can be engineered to provide not only a large surface area but also an abundance of unsaturated and reactive coordination sites. Using Mo[NMe2]4 and H2S as precursors, a desired thickness of amorphous MoS2 can be deposited on TiO2 nanotubes by atomic layer deposition. The identity and structure of the MoS2 film are confirmed by spectroscopic ellipsometry, X-ray photoelectron spectroscopy, scanning electron microscopy, and energy dispersive X-ray spectroscopy. The electrocatalytic performance of MoS2 is quantified as it depends on the tube length and the MoS2 layer thickness through voltammetry, steady-state chronoamperometry, and electrochemical impedance spectroscopy. The best sample reaches 10 mA/cm2 current density at 189 mV overpotential in 0.5 M H2SO4. All of the various geometries of our nanostructured electrodes reach an electrocatalytic proficiency comparable with the state-of-the-art MoS2 electrodes, and the dependence of performance parameters on geometry suggests that the system can even be improved further.
CRIS-Team Scopus Importer:2019-06-04

HfS2 thin films deposited at room temperature by an emerging technique, solution atomic layer deposition - Cao, Yuanyuan; Zhu, Sha; Bachmann, Julien (Dalton Transactions, 2021)
As a member of the two-dimensional metal dichalcogenide family, HfS2 has emerged as a promising material for various optoelectronic applications. Atomic layer deposition is widely used in microelectronics manufacturing with unique properties in terms of accurate thickness control and high conformality. In this work, a simple and versatile method based on the atomic layer deposition principles is presented to generate hafnium disulfide from the solution phase ('solution ALD' or sALD). For ease of comparison with the traditional gaseous atomic layer deposition (gALD) method, the same precursors are used, namely tetrakis-(dimethylamido) hafnium(iv) and H2S. The deposit is characterized on several different oxide substrates by spectroscopic ellipsometry, scanning electron microscopy, and X-ray photoelectron spectroscopy. In the saturated regime, the growth rate depends on the substrate nature and is between 0.4 and 0.6 angstrom per sALD cycle. This growth rate determined at room temperature is lower than with the gALD process reported at 100 degrees C recently. At those low deposition temperatures, the films remain in an amorphous state. This success in sALD expands the range of material classes available by the new method, adding transition metal dichalcogenides to the list containing oxides, cubic sulfides, hydrides, and organics so far. It promises to overcome the precursor constraints associated with the traditional gALD method, in particular the volatility requirement.
CRIS-Team WoS Importer:2021-09-03

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up

Stabilizing an ultrathin MoS2 layer during electrocatalytic hydrogen evolution with a crystalline SnO2 underlayer - Englhard, Jonas; Cao, Yuanyuan; Bochmann, Sebastian; Barr, Maissa; Cadot, Stéphane; Quadrelli, Elsje Alessandra; Bachmann, Julien (RSC Advances, 2021)

Utilizing the unique charge extraction properties of antimony tin oxide nanoparticles for efficient and stable organic photovoltaics - Liu, Chao; Félix, Roberto; Forberich, Karen; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Gu, Ening; Wortmann, Jonas; Zhao, Yicheng; Cao, Yuanyuan; He, Yakun; Ying, Lei; et al. (Nano Energy, 2021)
Simultaneously enhancing device performance and longevity, as well as balancing the requirements on cost, scalability, and simplification of processing, is the goal of interface engineering of organic solar cells (OSCs). In our work, we strategically introduce antimony (Sb3+) cations into an efficient and generic n-type SnO2 nanoparticles (NPs) host during the scalable flame spray pyrolysis synthesis. Accordingly, a significant switch of conduction property from an n-type character to a p-type character is observed, with a corresponding shift in the work function (WF) from 4.01 ± 0.02 eV for pristine SnO2 NPs to 5.28 ± 0.02 eV for SnO2 NPs with 20 mol. % Sb content (ATO). Both pristine SnO2 and ATO NPs with fine-tuned optoelectronic properties exhibit remarkable charge carrier extraction properties, excellent UV resistance and photo-stability being compatible with various state-of-the-art OSCs systems. The reliable and scalable pristine SnO2 and ATO NPs processed by doctor-blading in air demand no complex post-treatment. Our work offers a simple but unique approach to accelerate the development of advanced interfacial materials, which could circumvent the major existing interfacial problems in solution-processed OSCs.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Antimony doped tin oxide; Doping mechanism; Interface engineering; Metal oxide nanoparticles; Organic photovoltaics